DEVELOPING AN ISLAMIC FINANCIAL INCLUSION INDEX FOR ISLAMIC BANKS IN INDONESIA: A CROSS-PROVINCE ANALYSIS - M. Mahbubi Ali; Muhammad Rizky Prima Sakti; Abrista Devi (Journal of Islamic Monetary Economics and Finance, 2019)
This study measures an Islamic financial inclusion index in Indonesia based on three dimensions, namely the accessibility, availability and usage of Islamic banking services. Additionally, it measures the relationship between the Islamic financial inclusion index and the human development index (HDI). The study found that the level of Islamic financial inclusion in Indonesia is relatively low at the national level. DKI Jakarta is the most financially inclusive province in Indonesia, followed by East Java and Nanggroe Aceh Darussalam. In contrast, East Nusa Tenggara has the lowest average Islamic financial inclusion index. The findings also revealed a positive correlation between the Islamic financial inclusion index and HDI. Those provinces with the highest Islamic financial inclusion index were also likely to have a higher HDI. The findings of the present study suggest that both policymakers and the Islamic financial industry should play a greater role in improving financial access to low-income segments, especially in the eastern part of Indonesia such as East Nusa Tenggara and Papua provinces.